Analiza razpada Jugoslavije v luči nacionalizma: kako sta kontinuiteta nacionalističnih prerekanj etničnih političnih elit in etnično podjetništvo uničila večnacionalno Jugoslavijo - Flere, Sergej; Klanjšek, Rudi (University of Maribor Press, 2019)
Analysis of the Break-Up of Yugoslavia in the Light of Nationalism: How did the Continuity of Nationalist Disputes Among Ethnic Political Elites and Ethnic Entrepreneurship Destroy Multinational Yugoslavia. The book "Analysis of the Disintegration of Yugoslavia in the Light of Nationalism" deals with the dissolution of "Tito" of Yugoslavia from a political and historical standpoint, which the authors significantly supplement with studies of ethnicity and nationalism. The red thread of the work is the analysis of the workings of the elites, especially in terms of their frank and covert, even unconscious, nationalism. Indeed, these elites repeatedly believed that they were fighting nationalism while reinforcing it. As shown in the work, nationalism was thus hiding behind the ideas of brotherhood, egalitarianism, the idea that Yugoslavia had solved the problem of nationalism by its "nature". In this sense, the book represents a new attempt at a comprehensive analysis of the phenomenon, which is not only relevant to the field of Slovenia but also more broadly. Namely, it seems that understanding the functioning of multinational political entities has never been more current than it is today.